Belajar Shalat untuk Pemenuhan Kebutuhan Spiritual pada Anak Autism Spectrum Disorder (ASD) - Eflin Novita Sinaga; Fajar Utama Ritonga; Husni Thamrin (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Children with Special Needs (CSN) are children who have physical or psychological deficiencies. One example is children with Autism or Autism Spectrum Disorder (ASD). Autistic children have different spectrums in each child. Every child with ASD has unique characteristics; they all have neurological issues, but their preferences and ways of adapting to their environment vary from child to child. Children with ASD require special education or therapy to be trained to become independent in the future. Children with ASD are one type of CSN, and they, of course, require welfare services and will interact with social workers. Social workers will intervene using social work methods and provide programs to restore the social functioning of children with ASD. The goal of this fieldwork is a form of dedication to the community. Through the prayer learning that has been implemented, it is hoped that children with ASD will be able to meet their spiritual needs as religious individuals.